Análisis del desarrollo morfosintáctico en personas con Síndrome de Down en el periodo infantil y adolescente - Moraleda, Esther (Revista de Investigación en Logopedia, 2011)
Morphosyntax seems to be the weakest aspect of language in individuals with Down Syndrome, and is without doubt one of the aspects that needs most constant, systematic attention during speech and language therapy. Given the divergence between theories and hypotheses that set a chronological “ceiling” for language development and those that assume an evolution of language until adulthood, we believe it is important to conduct research on whether there are significant differences in the learning of morphosyntax depending on age. To this end, a morphosyntactic training program was carried out on 20 people with Down Syndrome, establishing two age bands: from 6 to 11 years and from 12 to 14 years of age. The results obtained show significant improvements in morphology and syntax in both age groups when they receive the morphosyntactic training program. These results support the idea that language may continue to develop beyond infancy and adolescence.
Keywords: Down syndrome; Morphosyntactic development; Speech and language therapy.